Paul Goodman and the Biography of Sexual Modernity - Churchill, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2010)
This article is a preliminary exploration of the relationship between the auto-biographical writings of radical US intellectual Paul Goodman and his theorizing of sexuality’s links to the project of political liberation. Goodman’s life writing was integrated into his social and political critique of mid-twentieth century society, as well as his more scholarly pursuits of psychology and sociology. In this way, Goodman’s work needs to be seen as generative of the dialectic of sexually modernity, which integrated intimate queer sexual experiences with conceptual, intellectual, and elite discourses on sexuality.